Case Report of Proliferative Peripheral Retinopathy in Two Familial Lissencephaly Infants with Miller–Dieker Syndrome - Shoukfeh, Omar; Richards, Alan B.; Prouty, Leonard A.; Hinrichsen, John; Spencer, William Rand; Langford, Marlyn P. (Journal of Pediatric Genetics, 2018)
A complete ophthalmic examination is not routinely performed on infants with Miller–Dieker syndrome (MDS, chromosome 17p13.3 microdeletion). The authors present the cases of four cousins with MDS who also carried a 16p13.3 microduplication (not associated with Rubinstein–Taybi syndrome). Retinopathy of prematurity-like proliferative peripheral retinopathy (PPR) was detected in two male first cousins, but was not detected in the female half-cousins. PPR in the first infant resolved by 4 months, but the second infant's PPR progressed, requiring photocoagulation followed by lens-sparing vitrectomy. While ocular abnormalities are more prevalent and severe in other lissencephalopathies, the PPR in these MDS infants underscores the sight-saving potential of performing an ophthalmologic exam with early molecular testing for all lissencephaly infants.
Keywords: agyria; LIS1 gene; pediatric; PDIA2; retina; SERPINF1